Review of invasive meningococcal disease during the last 40 years in Turkey - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2015)
Due to the lack of comprehensive surveillance data representing Turkey, the authors aimed to derive information by panoramically reviewing all articles related to invasive meningococcal disease (IMD) published in the last 40 years. The following databases were reviewed: Ulakbim (the national database), BIOSIS Previews (from 1995), Evidence-Based Medicine Reviews-Cochrane Database of Systematic Reviews (from 2005), Embase (from 1996), Ovid MEDLINE (R) (from 1946) and Journals@Ovid Full Text (2014). Twenty-seven articles, 10 published in international journals and 17 in national journals, were identified. Only two were multicenter sentinel meningitis surveillance studies. Also, 74% of IMD patients were aged 5 years or younger and the median overall case fatality rate during childhood was 18.44%. Turkey is a country where meningococcal vaccination on a national basis is recommended by WHO. A vaccination strategy for serogroups B and W135 targeting the first 5 years, covering especially the first 12 months, would be appropriate.
Keywords: epidemiology; invasive; meningitis; meningococcal; surveillance; Turkey; NEISSERIA-MENINGITIDIS; BACTERIAL-MENINGITIS; EPIDEMIOLOGY; SURVEILLANCE; VACCINE